Functional outcome of percutaneous screw fixation of intra-articular calcaneum fractures - Meena, Mahaveer; Sharma, Saksham; Jhanwar, Purushottam; Sharma, Shiv Bhagwan (International Journal of Research in Orthopaedics, 2018)
Background: The treatment of displaced calcaneum fractures has been a subject of intense discussion. Displaced intra-articular calcaneum fractures gives poor result with conservative treatment and requires reduction and internal fixation for favourable long term results. Open procedures are more prone to complications regarding wound healing. Percutaneous fixation offers a middle pathway in treating simpler variety of displaced calcaneal fractures. The aim of the study was to access the functional outcome of intra articular fracture calcaneum managed with closed reduction by Essex-Lopresti technique and percutaneous screw fixation. Methods: This study was done in department of Orthopaedics Jhalawar medical college and SRG Hospital Jhalawar, Rajasthan from January 2015 to January 2018. 26 intra-articular calcaneal fractures treated with closed reduction and percutaneous screw fixation under image intensifier. Results: 25 cases evaluated (one patient had lost follow-up), all fractures were united, average time of union was 8 weeks. The mean AOFAS score was 80 (range from 45 to 96), 9 patients had excellent, 12 patients had good, 3 patients had fair and one patient had poor result for that subtalar arthrodesis was done after one year of follow-up. Average Bohler’s angle 24.5 and Gissane angle was 120 degree. No clinically significant varus or valgus in any case (less then 5 degree). Conclusions: Treatment of intra-articular fractures of calcaneum is challenging but close reduction and internal fixation with 6.5 cannulated cancellous screws yields favorable outcome in majority of cases.